2021
DOI: 10.1002/elsa.202100046
|View full text |Cite
|
Sign up to set email alerts
|

Porous tal palm carbon nanosheets as a sensing material for simultaneous detection of hydroquinone and catechol

Abstract: In this article, an electrochemical sensor was prepared for the simultaneous detection of hydroquinone (HQ) and catechol (CT) by incorporating porous tal palm carbon nanosheets (PTPCNS) as the modifier substance on the surface of glassy carbon electrode (GCE). Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were utilized to characterize the electrochemical properties of the designed (PTCNS/GCE) sensor. PTPCNS/GCE demonstrated excellent electro‐catalytic property toward resolving the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Because tap water contains anionic species, such as SO 4 − , HCO 3 − , NO 3 − , and cations, such as Ca 2+ and Mg 2+ nitrite detection may be affected. [55][56][57] The CV technique was used to detect nitrites in tap water. Nitrite solutions of 300, 400 and 500 μM were used.…”
Section: Resultsmentioning
confidence: 99%
“…Because tap water contains anionic species, such as SO 4 − , HCO 3 − , NO 3 − , and cations, such as Ca 2+ and Mg 2+ nitrite detection may be affected. [55][56][57] The CV technique was used to detect nitrites in tap water. Nitrite solutions of 300, 400 and 500 μM were used.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, taffel plot analysis revealed that two electrons participate in the oxidation of HQ and CT. Hence oxidation of HQ and CT at Co 3 O 4 NR-GCE is a two proton and two electron transfer process [6].…”
Section: Probable Oxidation Mechanism Of Hq and Ct At Co3o4nr-gcementioning
confidence: 99%
“…There was no significant effect on the electrochemical response of HQ and CT for the metal ions and common ions. In cases of other similar structure of HQ and CT (phenol, 2-nitrophenol, 4-nitrophenol, resorcinol), CV was performed in 0.5 mM individual solutions in potential windows of 0-1 V, following reported procedures [6,44]. Phenol, 2-nitrophenol, and 4-nitrophenol did not respond at the modified electrode, while resorcinol showed an oxidation peak at 0.842 V, which was out of our potential window.…”
Section: Repeatability Stability and Interference Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, three-dimensional (3D) porous carbon nanosheet (PCN) networks with large exposed surfaces and heteroatom doping have great potential in EC sensors due to their surface characteristics including surface area, porosity, and electron/ion transport protocols. Additionally, the presence of sulfur (S), nitrogen (N), and metal doping in biomass materials results in an increase in the efficiency of a reaction due to more active sites in EC sensors, catalysis, fuel cells, energy storage, and so on. Because good bonding of heteroatoms can enhance sorption, excellent conductance, and rich surface wettability, abundant surface functional groups facilitate ion diffusions and rapid electron transfer kinetics in biological samples …”
Section: Introductionmentioning
confidence: 99%